INTER-RELIGIOUS DIALOGUE IN AISA- II - Thottakara, Augustine (Journal of Dharma, 2000)
This issue of the Journal also deals with Asia. The process, problems and prospects and the present state of affairs of inter-religious dialogue in some Asian countries are treated here.